Nanosponges: A Novel Trend for Targeted Drug Delivery - Jagtap, Sneha R.; Bhusnure, Omprakash G.; Mujewar, Imran N.; Gholve, Sachin B.; Panchabai, V.B. (Journal of Drug Delivery and Therapeutics, 2019)
Effective targeted drug delivery system has been a dream for a long time, but it has been largely frustrated by the complex chemistry that is involved in the development of new systems. Topical drug delivery system has many problems like poor permeability, skin irritation, allergic reactions etc. major problems of newly developed chemical entities is their poor solubility in water and pharmacokinetic issues. These poorly-water soluble drugs show many problems in formulating them in conventional dosage forms and the critical problems associated is its very low bioavailability. The invention of Nanosponge has become a significant step towards overcoming these problems. Nanosponge is tiny sponges with a size about a virus (250nm-1um), which can be filled with a wide variety of drugs. Nanosponge play vital role in targeting drugs delivery in a controlled manner. This sponge can circulate around the body until interact with specific target site and stick on surface and releasing drug in controlled manner both lipophilic and hydrophilic drugs are incorporated in nanosponge . Important characteristics of these sponges are their solubility in aqueous from and suitable for the drugs with poor solubility. This review is focusing on the preparation method, applications of nanosponge, factor in the field of drug delivery. Keywords: nanosponge, poor solubility, Biodegradable polymers, synthesis, preparation